ANALISIS DINAMIKA KETAHANAN PANGAN DI KABUPATEN JEMBER - Ahmad Anas; Rudi Wibowo; Yuli Haryati (University of Jember, 2008)
Food stability is not only in term of enough food availability but also capability to access including to buy food and there is no dependency to another countries. The research focused in Jember Regency. The research was aimed to explain that the enough food availability is not meant guarantee the food stability particularly for household rate. The analyze method that used are descriptive, stability food analyse that conducted by Sumarwan and Sukandar (1998) and Angka Kecukupan Gizi/AKG (nutrient sufficiency number) for household that including energy sufficiency rate and protein sufficiency rate. The results show that (1) the available food in Jember Regency in 1991 – 2006 for six commodity including rice and corn are surplus, whereas soybean, peanut, cassava and sweet potato are minus, (2) Arjasa and Jelbuk subdistrict are linear decreasing in stability food, (3) AKG average number in Panduman village, Jelbuk Subdistrict as 59,51% that meant have not food stability category, (4) AKG average in Puger Wetan Village, Puger Subdistrict as 80,39% that meant have food stability category. Keywords: Stability food, Availability food, Household stability food and AKG